The Ethical Philosophy of Kasb in Al-Ghazālī’s Economic Thought: A Classical Framework for Contemporary Reform - Purnamawati, Nina Wahidah (Islamicate Institute, 2024)
This article examines the concept of kasb (earning or acquisition) in the ethical and metaphysical framework of Abū Ḥāmid al-Ghazālī, one of the most influential scholars in Islamic intellectual history. Amid growing global calls for ethically grounded economic systems, Al-Ghazālī’s treatment of kasb in works such as Iḥyāʾ ʿUlūm al-Dīn, al-Iqtiṣād fī alIʿtiqād, and al-Munqidh min al-Ḍalāl offers a profound synthesis of spiritual intention, legal adherence, and socio-economic responsibility. This study uses a conceptual and qualitative methodology based on textual analysis of classical sources, supported by recent scholarly discourse on Islamic economics. The findings demonstrate that kasb is not merely a mechanism of material sustenance but a form of spiritual discipline, ethical striving, and communal contribution. Al-Ghazālī’s framework reconciles divine will and human agency, positioning lawful labor as an act of worship when performed with proper intention. Furthermore, this ethical paradigm provides a comprehensive model for reforming contemporary Islamic economic structures, emphasizing integrity, justice, and spiritual purpose. The research contributes to the revival of Islamic economic philosophy by integrating metaphysical insight with actionable ethics, offering an alternative to purely formalistic or profit-driven systems in the modern world.